SIMULATION AND STUDY OF MESO-METALLOPORPHYRIN ELECTRONIC PROPERTIES BY USING A DFT LOGARITHMS (ResearchJet Journal of Analysis and Inventions, 2022)
Some porphyrins and their metal complex (metalloporphyrin) play significant roles in sensing, photodynamic therapy, magnetic resonance imaging (MRI), anticancer drugs, electronic devices, and fluorescence imaging. In this study, the effect of changing the central metal was taken into consideration, as titanium metal and cadmium metal were used. In addition to adding chlorine atoms to the central metal, as well as studying the effects of different ends of the compound, once by making hydrogen at the meso-ends and again by making phenol rings at the meso-ends. And knowledge of all previous effects on electronic properties and their improvement. For example, the energy of filled and empty orbitals, the energy gap, hardness, softness chemical electronegativity, and electrophilicity are calculated. It can be seen that the selected materials have a lower energy gap than the original porphyrin. This result is very important. The energy gap of the compounds studied, all of which are located in the semiconducting region (1.109352 - 2.91692 eV), can therefore be used in important electronic applications such as sensors and solar cells. All calculations were carried out with the Gaussian 09 software package and in accordance with the density functional theory.